(untitled) (TEL Tempo, Espaço e Linguagem, 2026)
This essay analyzes the different conceptions of childhood in Brazil from a historical-political perspective, highlighting how race shapes the production of knowledge, institutional practices, and public policies aimed at Black children. By examining the period from colonial times to the Statute of the Child and Adolescent, the text problematizes the processes of violation that have more intensely affected Black childhoods. It emphasizes the persistence of racism in the denial of the right to childhood, as well as the need to deepen research and debates on Black childhoods.